Turmeric: The Ultimate Health Elixir for a Balanced Life - Chatterjee, Bandana (Innovations in Biological Science Vol. 6, 2024)
Turmeric, scientifically known as Curcuma longa, is a vibrant orange-yellow spice that has been a staple in cuisines worldwide for its distinctive flavour and numerous health benefits. Originating from South Asia, particularly India, turmeric is revered not only for its culinary uses but also for its medicinal and cosmetic properties. Rich in nutrients like fibre, calcium, iron, and potassium, turmeric is hailed as a superfood for its wide-ranging health benefits, including anti-inflammatory and antioxidant properties. This article provides an overview of the various forms of turmeric, including raw, ground powder, essential oil, and paste, along with their uses and nutritional content. Additionally, it explores the differences between white and yellow turmeric and offers insights into selecting high-quality turmeric products. Furthermore, the article delves into the diverse types of turmeric available in India, highlighting the nutritional composition and unique features of each variety. Special emphasis is placed on Lakadong turmeric, renowned for its exceptionally high curcumin content and therapeutic properties. From improving liver function to reducing the risk of chronic diseases, turmeric offers a myriad of health benefits, making it an essential addition to a healthy lifestyle. However, it is essential to be mindful of potential side effects and precautions while incorporating turmeric into one's diet or skincare regimen. Overall, turmeric stands as a versatile and indispensable ingredient that not only enhances the flavour of dishes but also promotes overall well-being and vitality.